Aspectos comparativos na produção de suínos machos submetidos a imunocastração ou castração cirúrgica - Muniz, Henrique da Costa Mendes (2019)
Three studies were conducted to compare productive aspects of male pigs submitted immunocastration or castrated surgically. The first study aimed to compare the requirements of digestible lysine, generated from the use of three factorials methods. In the second, the objective was to evaluate the carcass characteristics, bonus index, meat quality, weight of the main cuts and acceptability of products from pigs immunocastrated and castrated surgically. In the third, the objective was to compare the water disappearance, the wastage and ingestive behavior of water between male pigs immunocastrated and surgically castrated. We conclude in the first study that there is a difference between the factorials methods used and that pigs submitted to immunocastration generally require a higher amount of lysine by the three methods, besides having lower feed intake, greater weight gain and better feed conversion. Furthermore, it was observed that, in the period after the second dose of vaccine increases your feed intake. In the second study, it was concluded that immunocastrated male pigs, have a higher slaughter weight and lower carcass yield, as well as lower water holding capacity, lighter and less redness meat, but values for shear force similar to that of castrated males. The bonus index in both sexual categories was higher than “1” and there was no difference in the weight of the main commercial cuts. Sensory analysis showed no difference in consumer acceptability of products manufactured from castrated or immunocastrated pigs. Finally, the third study allowed to conclude that immunocastrated pigs have less disappearance and water wastage in relation to the castrated ones and the daily behavior of water disappearance, of both sexual categories is bimodal, with greater disappearance of water in the afternoon.